KARAKTERISTIK BUBUK EKSTRAK KULIT BUAH JERUK MANDARIN (Citrusreticulata)PADA PERLAKUAN LAMA MASERASI DAN KONSENTRASI MALTODEKSTRIN - Elisabet Silalahi, Siska; Wrasiati, Ni Luh Putu; Dewi Anggreni, Anak Agung Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 1 (2015): Maret)
The aimed of this research were 1) determine the effect of maceration time and maltodextrin concentration on the characteristics of mandarin citrus peel extract powder, 2) find out the maceration time and maltodextrin concentration to obtain the best characteristics of the mandarin citrus peel extract powder. This study used a factorial randomized block design. The first factor was maceration time consists of 4 levels, namely: 6, 12, 18 and 24 hours, and the second factor was maltodextrin concentration which consists of 3 levels: 10, 15 and 20 %. Each treatment was done 3 times. The parameters tested include yield, solubility, sensory testing. The results showed that maceration time had no significant effect on the yield and solubility of mandarin citrus peel extract powder. Maltodextrin concentration effect had signifcant on the yield and solubility of mandarin citrus peel extract powder. Treatment interaction between maceration time and maltodextrin concentration had significant effect on taste preferences, the strength of taste, flavour preferences, and flavour strength. However, no significant effect on yield and solubility of mandarin citrus feel extract powder. 6 hours maceration time and 10% maltodextrin concentration produced the best characteristics of mandarin citrus peel extract powder, include: yield 42.91%, solubility 99.75%, taste preferences 6.13 (between like until very like), the strength of taste 2.07 (between strong to strong a bit), aroma preferences of 5.27 (between like a bit to like), the strength of the aroma of 1.53 (between very strong to strong).
Keywords: 33,